Cannabis use during pregnancy: effects on mother and child - Arneja, Ashmeen; Dhillon, Jasmeen; Kirandeep; Khandelwal, Vaibhavi (My University, 2026)
Background: Cannabis use during pregnancy and breastfeeding has increased since legalization. Many individuals view cannabis as natural or low risk and use it to manage nausea, stress, sleep issues, pain, or mental-health concerns. However, THC crosses the placenta and enters breast milk, raising concerns about fetal and infant neurodevelopment. Aim: To examine factors influencing cannabis use during pregnancy or breastfeeding and summarize current evidence on maternal and infant outcomes. Methods: A literature review was conducted using CINAHL, PubMed, and Google Scholar. Search terms included “maternal cannabis use,” “prenatal cannabis,” “breastfeeding AND cannabis,” and “pregnancy AND THC.” Limiters were English, 2019–2025, peer-reviewed research. Ten studies were included, representing systematic reviews, surveys, qualitative studies, cohort analyses, and mechanistic research. Results: Findings show that decisions about cannabis use are shaped by peer experiences, perceived safety, and fear of judgment, emphasizing the need for supportive counselling. Evidence indicates modern cannabis products contain higher THC concentrations, increasing exposure risks. Prenatal or breastfeeding cannabis use is associated with low birth weight, smaller head circumference, cognitive and behavioural challenges, and possible long-term vulnerability to substance use. Individuals with adverse childhood experiences may have higher cannabis use rates, suggesting underlying psychosocial needs. Cannabis also passes into breast milk and may alter its nutritional and immune-related components. Implications for Nursing Practice: Nurses play a key role in providing nonjudgmental, evidence-based education, screening, and harm-reduction support. Strengthened public health messaging, along with further research on dose, frequency, and potency, is needed to guide pregnant and breastfeeding individuals.
Presented on April 23, 2026, at Student Research Day, held at MacEwan University in Edmonton, AB and on January 29, 2026, at the Canadian Nursing Students' Association (CNSA) National Conference, held at Delta Hotels in Saskatoon, SK.
Keywords: cannabis; pregnancy; breastfeeding; development